Pemanfaatan Selulosa dari Rumput Gajah (Pennisetum purpureum) pada Sintesis Karboksimetil Selulosa (CMC) : [Utilization of Cellulose from Pennisetum purpureum at The Synthesis of Carboxy Methyl Cellulose (CMC) - Erwin Abdul Rahim; Grace Sita Turumi; Syaiful Bahri; Jusman; Syamsuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Cellulose from Pennisetum purpureum has been used as the main ingredient in the synthesis of carboxymethyl cellulose (CMC). The purpose of CMC synthesis from the cellulose of Pennisetum purpureum is to obtain CMC compounds with the best degree of substitution (DS) value and the highest yield. The study was conducted using a completely randomized design with a factorial pattern consisting of two independent variables, namely the concentration of trichloroacetic acid (10%, 20%, and 30%) and reaction time (3 and 4 hours). The results showed that the CMC with the highest DS value (0.839) was obtained using 20% trichloroacetic acid with a reaction time of 3 hours. The highest CMC yield was 30.15% which was obtained using 30% trichloroacetic acid with a reaction time of 4 hours. Keywords: Pennisetum purpureum, carboxymethyl cellulose, substitution degree.